2008
DOI: 10.1007/s10552-008-9154-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of educational background and breast cancer among Japanese women

Abstract: The present results suggested that cancer prevention strategies should recognize women with a higher educational level as a high risk group for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…(Heck and Pamuk, 1997;Braaten et al, 2004;Fujino et al, 2008;Palmer et al, 2012). The present study found that reproductive factors were distributed differentially across different levels of education.…”
Section: Discussionsupporting
confidence: 47%
“…(Heck and Pamuk, 1997;Braaten et al, 2004;Fujino et al, 2008;Palmer et al, 2012). The present study found that reproductive factors were distributed differentially across different levels of education.…”
Section: Discussionsupporting
confidence: 47%
“…After World War II, the number of women in the Japanese workforce has risen,45 which has produced a declining birthrate 46,47. This societal shift may have resulted in relevant changes in the population distribution of breast cancer risk factors, such as higher socioeconomic status,48 higher body mass index, fewer births, and later age at first birth 42,49. Consequently, breast cancer risk profiles may be more similar for foreign- and US-born Japanese women than for other Asian populations, causing a narrowing in the incidence rate gap between Japanese immigrants to the United States and those who are US-born.…”
Section: Discussionmentioning
confidence: 99%
“…Since World War II, the number of women in the Japanese workforce has risen,66 leading to a declining birth rate 67,68. This societal shift may have resulted in changes in the population distribution of breast cancer risk factors such as higher SES,69 higher body mass index, lower parity, and later age at first birth,68,70 as well as in factors that may affect survival. This may explain why foreign- and US-born Japanese women were more similar than were immigrant and nonimmigrant members of the other Asian populations we studied.…”
Section: Discussionmentioning
confidence: 99%